A Study of Diphtheria Bacilli, with Special Reference to their Serological Classification - Smith, J. (1923)
Much work has already been done in connection with the differentiation of true diphtheria bacilli from diphthomorphic organisms. Some observers have maintained that all disease producing strains could be distinguished from non-pathogenic types by their sugar reactions. Others have laid much stress on some particular forms of virulence test. More recently serological classification has been attempted in order to help to solve this problem. With regard to sugar reactions Graham-Smith (1908) found that certain strains produced acid in media containing saccharose, while Hine (1913), on the other hand, maintained that no true diphtheria bacillus could ferment this sugar. Eagleton and Baxter (1922) have shown that diphtheria bacilli, virulent and non-virulent, ferment glucose but do not produce any change in saccharose. Jordan and his collaborators (1922) have found that virulent and non-virulent bacilli fermented glucose and maltose and produced no change in saccharose and that their action on dextrin was variable. Work on the serological classification of these organisms has also shown some considerable variation. Havens (1920) isolated 206 strains of diphtheria bacilli. These represented cultures from acute cases, release cultures and cultures from healthy carriers. He found that these 206 strains could be divided into two serological groups, one group containing 169 strains, the other 37. There was no evidence of any cross agglutination. Durand (1920) isolated 255 strains of typical diptheria bacilli and after excluding those strains which would not form stable suspensions divided them into five groups, A. B. C. D. and E. containing 16, 8, 25, 61 and 40 strains respectively. Eighty-seven strains were found to be inagglutinable by these five sera but nevertheless could absorb agglutinins from such sera. His final figures for the five groups of bacilli are 18, 8, 31, 76 and 51. Durand and Guerin (1921) in a further paper showed that small isolated outbreaks were always due to the same type of bacillus. They also found that healthy carriers gave the same type of bacillus as was found in the cases arising from these sources of infection. Bell (1922) isolated 133 strains of B. diphtheriae indifferently collected from cases and carriers. He was able to agglutinate 80 per cent. of these strains by three monovalent sera. Group I contained 17 strains, Group II 8 strains, Group III 80 strains. In view of the results which have just been described it has appeared important to investigate further a considerable number of strains as encountered in routine work, not only as regards the serological characteristics of the organisms but also in regard to their morphology, their biochemical reactions, and their virulence for guinea-pigs.